2008
DOI: 10.1016/j.foodchem.2008.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of antiradical phenolic constituents from fourteen edible Myrtaceae fruits

Abstract: Many species of Myrtaceae are cultivated in home gardens throughout the tropics for their edible fruit, and have been used in traditional medicine to treat several inflammatory conditions. Fruit phenolics are important dietary antioxidant and anti-inflammatory constituents. We have investigated the antiradical activity, total phenolic content (TPC), and total anthocyanin content (TAC) of 14 underutilized Myrtaceae fruits, namely Eugenia aggregata, E. brasiliensis, E. luschnathiana, E. reinwardtiana, Myrciaria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
187
6
52

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(261 citation statements)
references
References 38 publications
16
187
6
52
Order By: Relevance
“…13 Ursolic acid has been isolated from the leaves of E. brasiliensis 14 and anthocyanins, ellagic acid, myricetin, quercetin, quercitrin and rutin have also been detected in the fruits. 15 Our studies have shown that the essential oil extracted from the leaves of E. brasiliensis has an appreciable antibacterial activity, 16 while the crude hydroalcoholic extract of the leaves and fractions has anti-inflammatory activity. 17 The use of a simple microorganism such as Artemia salina to test in vivo lethality can represent a simple tool for guiding the screening and fractionation of physiologically active plant extracts.…”
Section: Introductionmentioning
confidence: 87%
“…13 Ursolic acid has been isolated from the leaves of E. brasiliensis 14 and anthocyanins, ellagic acid, myricetin, quercetin, quercitrin and rutin have also been detected in the fruits. 15 Our studies have shown that the essential oil extracted from the leaves of E. brasiliensis has an appreciable antibacterial activity, 16 while the crude hydroalcoholic extract of the leaves and fractions has anti-inflammatory activity. 17 The use of a simple microorganism such as Artemia salina to test in vivo lethality can represent a simple tool for guiding the screening and fractionation of physiologically active plant extracts.…”
Section: Introductionmentioning
confidence: 87%
“…The plant belongs to Myrtaceae family and grows naturally in clayey loamy soil in tropical as well as in sub-tropical zones of Indo-gangetic plains. These species are reported to be very rich in tannins, flavonoids, essential oils, anthocyanins and other phenolic constituents (Sharma et al 2003;Reynertson et al 2008). The purple coloured fruits are available abundantly during summer season for a short span of time, causing a seasonal glut.…”
mentioning
confidence: 99%
“…Anthocyanin content was determined by the pH differential method. 18,23 Pigment concentration was expressed as g L -1 of cyanidin 3-glucoside. All measurements were performed in triplicate.…”
Section: Determination Of Phenolic Compoundsmentioning
confidence: 99%